Involvement of Santafe’s Rabble at the dawn of Independence - Pérez, Robert Ojeda (Universidad Santo Tomás, Bogotá, Colombia, 2011)
This article intends to demonstrate the several ways of involvement that Santafé’s rabble had against the power excessess of the colonial system. Historiography has placed as starting point of the independence process a historical fact like the one ocurred on July 20th 1810. It has also pointed out the involvement of the criollos elite as sole agent in that process. This article invites to relect on other subjects, who were also agents in the process of independence and from many years back. A series of case studies is exposed. These are part of a more complex empiric research, to support this relection on the involvement of Santafe’s rabble at the dawn of Independency.